Design and implementation of programmable logic array using crossbar structure in quantum‐dot cellular automata. (23rd August 2021) - Zhu, Chunsong; Xie, Guangjun; Zhang, Yongqiang
Abstract: Quantum‐dot cellular automata (QCA) is a promising nanoelectronic technology having the characteristics of stable operation, breakneck speed, and ultralow energy consumption in theory. However, no scalable and modular architecture can facilitate circuit implementation, restricting the overall development of this technology. Different from the traditional programmable logic array (PLA) using AND‐OR arrays, this paper proposes a design method of PLA using crossbar structure in QCA. The PLA consists of multiple programmable units in which the majority gates can be programmed as AND/OR gates, and an inverter following each majority gate will invert the output as needed. To flexibly adjust the logic states of each programmable unit, a programmable clock scheme and N ‐bit latch are then proposed. Therefore, a circuit can arbitrarily be achieved by programming the PLA. Four circuits, including full adder, 2–1 MUX, D flip‐flop, and 1‐bit memory, are designed, implemented, and simulated in QCA, by using this PLA. Experimental results show that the designed circuits realize logic functions correctly and stably. Abstract : This paper proposes a new design method to programmable logic array (PLA) in QCA by using crossbar structure. The PLA consists of multiple programmable units, which are composed of a majority gate and an inverter to be connected in an orderly manner. Thus, a circuit can arbitrarily be achieved by programming the PLA.